2019
DOI: 10.1111/eff.12467
|View full text |Cite
|
Sign up to set email alerts
|

Migratory gauntlets on oceanic islands: Watershed disturbance increases the cost of amphidromy

Abstract: Migratory fishes can be threatened by conditions encountered along dispersal pathways that impede access to feeding or breeding grounds. In this study, we tested the hypothesis that amphidromous fishes are equally or more sensitive to conditions along dispersal pathways than conditions in primary residential habitats. We did so by conducting distribution‐wide population surveys of all five amphidromous gobies native to the Hawaiian Islands to assess responses to in‐stream habitat, invasive species and watershe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Care should, of course, be taken to focus efforts on key stream segments in order to deliver the greatest benefits to local populations. While this might call for targeting habitat used by stream residents for feeding and reproduction, it might be necessary to focus on downstream migratory corridors, including estuarine and nearshore coastal areas that may influence immigration and recruitment (Blum et al ., ; Hain et al ., ; Walter et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Care should, of course, be taken to focus efforts on key stream segments in order to deliver the greatest benefits to local populations. While this might call for targeting habitat used by stream residents for feeding and reproduction, it might be necessary to focus on downstream migratory corridors, including estuarine and nearshore coastal areas that may influence immigration and recruitment (Blum et al ., ; Hain et al ., ; Walter et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, it would be prudent to protect, improve, or create in‐stream habitat for non‐migratory residents in order to buffer against unfavourable marine environs, which are not as responsive to management interventions ( i.e ., due to a mismatch in scale). Appropriate actions might include restoring base flows, maintaining water quality, removing invasive species that compete or prey upon native larvae, preserving habitat diversity so that non‐migrant fishes of multiple species can complete their life cycles in‐stream (Blum et al ., ; Brasher, ; Hain et al ., , ; Heim‐Ballew, ; Lisi et al ., ; Walter et al ., ). Care should, of course, be taken to focus efforts on key stream segments in order to deliver the greatest benefits to local populations.…”
Section: Discussionmentioning
confidence: 99%
“…Though the oceanic dispersal model and otolith analyses both indicated that some watersheds were better positioned to receive ocean‐going larvae than others, we found that the observed proportion of freshwater residents was not correlated with stream‐scale average or variation in larval settlement rates. This mismatch could reflect the simplifying assumptions of the model (Moody et al, 2019 ), such as equal input of larvae to the ocean from every stream, no postsettlement filters upon survival of recruiting postlarvae in streams (Hain et al, 2019 ), and no variation among streams in their capacity to attract marine larvae as they approach the shore. However, the stream‐level mismatch could also be unrelated to passive oceanic dispersal but instead reflect differences in the survival of resident larvae or the efficiency of delivering hatchling larvae to the coast.…”
Section: Discussionmentioning
confidence: 99%
“…The available surveys of mitochondrial haplotype variation suggest no geographic structure among islands or watersheds (Alda et al, 2016 ; Chubb et al, 1998 ), so alleles for either fixed residency or full plasticity could spread easily in A. stamineus . Invasive predatory fishes are common in most Hawaiian streams (Hain et al, 2019 ; Moody et al, 2017 ), and they could impose strong selection against freshwater residency. However, the resident strategy could yield high fitness in streams where the lack of predators creates a safe environment for all life stages.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, their larvae are unaffected by in‐stream control measures while they are at sea, whereas the invasive fishes linked to their decline reside in streams throughout their life. Our model focusses on 'o'opu nōpili ( Sicyopterus stimpsoni ), an endemic freshwater goby, and invasive live‐bearing fishes (poeciliids, including guppies, mollies, mosquitofish and swordtails) that numerically dominate many invaded streams in Hawaii (Moody et al., 2017) and affect S. stimpsoni populations (Hain et al., 2019). We used field data and biological intuition to select plausible parameters for a generic stream network with a total length of 5 km and an average width of 2 m (Table S2).…”
Section: Case Study: Invasive Fishes In Hawaiian Streamsmentioning
confidence: 99%